In vitro kinetic parameters of marandu palisadegrass associated with nonfiber carbohydrates - Perivaldo Carvalho; Luciano da Silva Cabral; Nelcino Francisco de Paula; Isis Scatolin de Oliveira; Rodrigo Dias Lauritano Pacheco; Mariane Moreno Ferro; Arthur Behling Neto; Bruna Gomes Macedo; Isabela Eloisa Bianchi; Karine Dallavecchia Camargo (Semina: Ciências Agrárias, 2016)
This study aimed to evaluate the effects of different levels (0, 10, 20 and 30%) of starch or glucose associated with marandu palisadegrass (Urochloa brizantha cv. Marandu) on its kinetic parameters and fiber digestion by the in vitro gas production technique. The experiment was arranged in a completely randomized design, with four treatments and six replications for each energy source. The marandu palisadegrass associated with nonfiber carbohydrate levels was incubated in 120 ml bottles, with McDougall buffer and rumen fluid from two rumen-cannulated sheep. Readings were taken of gas pressure within the bottle, and two vials were removed at 24, 48 and 96 hours (h) to assess residual neutral detergent fiber (NDF). The one-pool logistic model was used to estimate the kinetic parameters for pure forage and forage associated with starch, however it was necessary to use the two-pools model when glucose was added. Each 1% of added starch promoted a linear increase in total gas production of 0.2254 ml and a decrease in lag time of 0.2451 h, but did not affect the digestion rate. Glucose levels had a quadratic effect on digestion rate and lag time, with a minimum estimated value for digestion rate of 0.01689 h-1 at a glucose level of 10.07% and a minimum lag time of zero. Starch levels caused a linear reduction in NDF digestion of 0.296% only at 24 h, while glucose levels linearly reduced the NDF digestion in all evaluated times (0.3269, 0.4171 and 0.2340% at 24, 48 and 96 h, respectively). Glucose levels promoted different effects on the in vitro gas production kinetic parameters of marandu palisadegrass compared to starch supplementation, highlighting the prolonged negative effects on NDF digestion.